Malaysian women in management - Noor Rahamah Hj Abu Bakar, (Faculty of Social Sciences and Humanities, UKM,Bangi, 2012)
Malaysian women account for about 34.0 percent of all employed workers in 1999 yet their entry into the workplace has by no means guaranteed them access to top jobs. This paper discusses the distribution patterns of Malaysian women in management from the year 1970 to 1999 using secondary data to take a closer look at their role as a family manager, and by means of a field study, examines how Malaysian women managers conduct themselves when managing, and explores ways of enhancing Malaysian women’s participation in management. Findings point to the imperative of helping the dual-career woman cope with the domestic and work environment through the provision of such conveniences as flexible working hours, and financially accessible child care facilities. Suggestions to support career women advancement into management positions include career planning, counseling and training, senior management mentoring, helping male workers to come to terms with women managers, and the creation of informal support networks for women managers.